2006
DOI: 10.1124/jpet.106.105874
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Mediated Protein Haptenation of Dapsone and Sulfamethoxazole in Human Keratinocytes: II. Expression and Role of Flavin-Containing Monooxygenases and Peroxidases

Abstract: Arylamine compounds, such as sulfamethoxazole (SMX) and dapsone (DDS), are metabolized in epidermal keratinocytes to arylhydroxylamine metabolites that auto-oxidize to arylnitroso derivatives, which in turn bind to cellular proteins and can act as antigens/immunogens. Previous studies have demonstrated that neither cytochromes P450 nor cyclooxygenases mediate this bioactivation in normal human epidermal keratinocytes (NHEKs). In this investigation, we demonstrated that methimazole (MMZ), a prototypical substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 34 publications
2
58
0
Order By: Relevance
“…Although lactoperoxidase (Gorlewska-Roberts et al, 2004), myeloperoxidase (Uetrecht et al, 1993), and thyroid peroxidase (Gupta et al, 1992) have been shown to bioactivate arylamines to reactive metabolites in vitro, none of these enzymes seems to be expressed in cultured human KCs (Vyas et al, 2006b). However, it is noteworthy that peroxidase inhibition reduces the bioactivation of dapsone in human KC cultures (Vyas et al, 2006b)-substantiating a role for peroxidases in cutaneous bioactivation. Further studies are needed to identify the specific peroxidases expressed in human skin and skin cells.…”
Section: Evidence For the Expression Of Drug-metabolizing Enzymes In mentioning
confidence: 90%
See 2 more Smart Citations
“…Although lactoperoxidase (Gorlewska-Roberts et al, 2004), myeloperoxidase (Uetrecht et al, 1993), and thyroid peroxidase (Gupta et al, 1992) have been shown to bioactivate arylamines to reactive metabolites in vitro, none of these enzymes seems to be expressed in cultured human KCs (Vyas et al, 2006b). However, it is noteworthy that peroxidase inhibition reduces the bioactivation of dapsone in human KC cultures (Vyas et al, 2006b)-substantiating a role for peroxidases in cutaneous bioactivation. Further studies are needed to identify the specific peroxidases expressed in human skin and skin cells.…”
Section: Evidence For the Expression Of Drug-metabolizing Enzymes In mentioning
confidence: 90%
“…The N-hydroxylation of dapsone and sulfamethoxazole in cultures of KCs is somewhat surprising in view of the absence of CYP2C9 expression in these cells (Reilly et al, 2000). Although CYP2C9 is the enzyme responsible for the N-hydroxylation of these drugs in liver, it seems that FMO3 and peroxidases are responsible for this metabolism in KCs (Vyas et al, 2006b). Because the arylhydroxylamine metabolites of these drugs are believe to be involved in the provocation of an immune response (Cribb et al, 1996), this observation suggests that local biotransformation may be important in these reactions in the skin.…”
Section: Evidence For the Metabolism Of Drugs In Skin And Skin Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DUOX1 is known to play a role in supplying H 2 O 2 to thyroperoxidase and lactoperoxidase in thyroid and nonthyroid tissues, respectively (34), it was unlikely that DUOX1 plays either of these roles in NHEK, because Vyas et al (35) have clearly demonstrated the lack of thyroperoxidase or lactoperoxidase in NHEK.…”
Section: Discussionmentioning
confidence: 99%
“…Because peroxidases and FMO have been shown to bioactivate DDS and SMX in human epidermal keratinocytes (Vyas et al, 2006b), leading to protein haptenation, we sought to determine the role of these enzymes in the DDS-specific protein haptenation in naive KG-1 cells. For this purpose, naive KG-1 cells were exposed to DDS in the presence or absence of a peroxidase inhibitor (ABH) or a competitive substrate for FMO (MMZ).…”
Section: Resultsmentioning
confidence: 99%